(untitled) (Raparin Journal of Humanities (RJH), 2024)
This study explores the life of a great scholar among the scholars of Islamic world. This distinguished scholar، who has spent nearly sixty years in serving knowledge and science، has written many valuable books. Consequently، his writings have offered a great service to the Islamic library and many great scholars were learned and educated on his hands. In this research an intensive investigation has been made on those footnotes that this scholar has written on a number of the holy Quran verses، in the interpretation “the places of knowing the holy Quran and explaining its truth” that was written by Abdulla Ibn-Ahmed Al-Nafasy. It is considered as one of the valuable books. It has an accurate academic style and only a group of exceptional scholars can understand it، for understanding the terms and concepts they are in need of these footnotes that “Gozapanky” Scholar has written. The study resolves these footnotes which mostly have been taken from sources، footnotes and reliable enlightenments for explaining “the places of knowing the holy Quran and explaining its truth”. Accordingly، it was done by rewriting the text as the writer wanted to be، then confirming the academic material from various aspects of the reliable sources، and simplifying these footnotes for readers and researchers، as a service and an easier way of taking benefit from it. The research explains the unknown aspects of the author’s life and unobvious places of the footnotes. It also referred the derived quotes to their owners as it is required in a scientific research. This paper comes up with a number of results which in general benefit all the researchers of the Kurdish scholar lives and their efforts and this great scholar in particular، including: “Mala Salh Gozapany” has been an educator، a Daii، a teacher and a Mufti، too ،The footnotes involve quoting، collecting، making concise that solve the difficult and the vague terms،The author، in his footnotes، has combined the interpretation of the Prophet companions and his interpretation These footnotes mention those distinguished signs that are taken from the holy Quran and the interpretation of “the places of knowing the holy Quran and explaining its truth”.